Effects of carbon nanomaterials on the migration and fate of organic pollutants in the ecological environment. Issue 1 (2nd January 2021) - Chen, Guobin; Yuan, Hengyi
Abstract: The purpose of this study was to investigate the mechanism of adsorption reaction between heterocyclic organic compounds with different number of ring atoms and different atoms replacing carbon atoms and carbon nanotubes with different surface functional groups. Based on the current situation of research on adsorption of carbon nanomaterials adsorbing organic pollutants, the existing problems and limitations were analyzed by studying the properties and characterization of single-walled carbon nanotubes, oxidized single-walled carbon nanotubes and non-porous graphite powder, such as elemental analysis, transmission electron micrograph, zero charge point, etc. The three adsorption materials were investigated by batch experiment. Six compounds of thiophene, pyrimidine, benzene, aniline, 2-aminopyrimidine and 4, 6-diaminopyrimidine were selected as the adsorbate for detecting adsorption capacity. The results showed that the affinity of different adsorbents on different adsorbents varied greatly. The adsorption capacity of heterocyclic compounds containing N and S was greatly enhanced by non-hydrophobic action. And the degree of oxidation of the adsorbent and the ph of the solution determined the adsorption capacity of the adsorbent for nitrogen-containing heterocyclic compounds. Therefore, in the ecological environment, the migration of hydrophilic organic pollutants in the environment can be reduced by the preparation of appropriate carbon nanotubes.